PENGARUH DARI BEBERAPA HORMON TUMBUHAN TERHADAP PERFORMA AYAM BROILER (Gallus domesticus) - Densfor Simanjuntak; Meriksa Sembiring; Alfath Rusdhi (Bajang Institute, 2025)
The aim of this research is to determine the effect of different plant hormones on the performance of Broiler chickens (Gallus domesticus). The data analysis method used in this study is a Completely Randomized Design (CRD) Non-Factorial, which consists of 5 treatments and 4 replications: H0 (Control), H1 (Neobro), H2 (banana stem hormone), H3 (sprout hormone), and H4 (sweet potato shoot hormone). The parameters observed in this study are feed consumption, body weight, and feed conversion. The results indicate that the H2 treatment (banana stem hormone) was the best treatment based on the observations of feed consumption, body weight, and feed conversion. The effect of several plant hormones on the performance of broiler chickens (Gallus domesticus) was as follows: average feed consumption of 2.12 kg/head, body weight of 1.67 kg/head, and feed conversion of 1.27